Remote work burnout, professional job stress, and employee emotional exhaustion during the COVID-19 pandemic - Costin, Alina; Roman, Alina Felicia; Balica, Raluca-Stefania (Frontiers in Psychology, 2023)
Relevant research has investigated how organizational support systems, remote work adaptation, and control over scheduling reduced psychological burnout and occupational stress, improving employee wellbeing during the COVID-19 pandemic. This systematic literature review has analyzed significant published peer-reviewed evidence in relation to how remote employees lacking constant organizational support during the COVID-19 outbreak experienced escalated job demands, professional strain, low satisfaction and performance, and increased burnout. Throughout February 2023, a quantitative literature review covering scholarly databases such as the Web of Science, Scopus, and ProQuest was performed, with the following search terms: “COVID-19” + “remote work burnout”, “professional job stress”, and “employee emotional exhaustion”. By inspecting research published between 2020 and 2022, 311 articles satisfied the eligibility criteria. Excluding sources in PRISMA terms, 44 empirical sources were finally selected. Methodological quality assessment tools such as AMSTAR (Assessing the Methodological Quality of Systematic Reviews), AXIS (Appraisal tool for Cross-Sectional Studies), MMAT (Mixed Methods Appraisal Tool), and SRDR (Systematic Review Data Repository) were employed. Data visualization tools (VOSviewer and Dimensions) integrating layout algorithms and bibliometric mapping were harnessed. The scope of this study does not advance how taking breaks and time management in a psychologically safe environment prevented remote work burnout and increased productivity during the COVID-19 pandemic. Subsequent analyses should develop on how remote-work time and stress management by use of burnout assessment tools resulted in coherent workplace behaviors and processes meeting organizational expectations and reducing emotional stress and workplace pressure.